Hypomineralised Second Primary Molars: Prevalence, characteristics and perception of management by Irish dentists - Mc Carra, Charlotte Anne (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2021)
Background: This thesis comprises three different studies with a shared focus on Hypomineralised Second Primary Molars (HSPM). Aims: Study 1: to investigate the global prevalence of HSPM by conducting a systematic review and meta-analysis. Study 2: to investigate the prevalence of HSPM in Dublin 4 6-year-old school children. Study 3: to explore how general dentists in the Republic of Ireland perceive and manage HSPM. Methods: Study 1: A comprehensive literature search was performed through MEDLINE/PubMed, Scopus and Web of Science databases. A meta-analysis was performed to determine the pooled worldwide prevalence of HSPM. Study 2: A cross sectional study was carried out using a sample of 4 6-year-old boys from one Dublin primary school. HSPM prevalence and dental caries were recorded by calibrated examiners (kappa ≥0.70). The association between dental caries prevalence and HSPM was tested using chi-square (α = 5%). Study 3: A validated structured questionnaire containing 19 questions on awareness, experience and clinical management of HSPM was sent to Irish dentists using Survey Monkey. Binary outcomes and independent variables were compared using logistic regression analysis (α = 5%). Results: Study 1: The search strategy identified 1,987 articles, 486 were retrieved for full text evaluation and 37 studies were included in the meta-analysis. The prevalence of HSPM was 6.8% (95%CI: 4.98-8.86%) on a child level and 4.08% on a tooth level (95%CI: 2.80-5.59%). The diagnostic criteria used did not influence the prevalence results (p≥.05). Study 2: A total of 81 children were examined and 31 had HSPM defects (38.27% prevalence). The mean number of affected teeth per child was 2.16±1.13. The most common defects were creamy-white demarcated opacities (81.8% of affected teeth). No association was found between caries experience and HSPM prevalence (p= .25). Study 3: A total of 356 (279 general dentists; 66 specialists) responded to the survey. The awareness of HSPM was reported by 72.40% of dentists and the majority were confident in diagnosing HSPM (70.79%). Dentists who had practiced for ≥ 15 years were significantly more likely to document HSPM frequently compared to those with less experience (OR 0.29; p=.012). No significant association was found between age group, years of practice and workplace and confidence in HSPM diagnosis. The most cited barrier to care was child s behaviour. A broad variation was observed in the clinical scenarios with preventive treatments and biological approaches commonly selected options. Conclusions: Study 1: The present meta-analysis showed a HSPM prevalence worldwide of 6.8% on a child level and 4.08% on a tooth level. Study 2: The prevalence of HSPM in this sample was 38.2% and demarcated opacities were the most common form of the defect. The caries rate was high (22%) but there was no association with HSPM in this sample. Study 3: Irish dentists are aware of HSPM and are confident in diagnosis and management. Variation existed in treatment options reflecting the disparity that exists in clinical management.
APPROVED